NEW INSIGHT INTO THE MIDDLE EOCENE CALCAREOUS NANNOPLANKTON BIOSTRATIGRAPHY AND PALEOENVIRONMENT FROM FAYOUM AND BENI SUEF AREAS, EGYPT (Rivista italiana di Paleontologia e Stratigrafia, 2023)
The present study deals with calcareous nannoplankton paleoenvironmental and biostratigraphic implications as well as the genesis and the stratigraphic significance of an event bed recognized from the middle Eocene Beni Suef Formation in the sections of Gebel Na’alun (Fayoum area) and Gebel Homret Shaibun (Beni Suef area), Egypt. Calcareous nannoplankton biostratigraphy indicates that the Beni Suef Formation in the two areas is synchronous, covering an interval that may be correlated with the calcareous nannoplankton Zone NP17. Paleoenvironmental implications from calcareous nannoplankton suggests deposition of sediments in the Beni Suef Formation under relatively stable, temperate and mesotrophic conditions, with a short interval of eutrophication in the basal part of the Homret Shaibun section.